Application of Fuzzy Logic to Determine the Condition of Candy Packaging Seals Based on Temperature, Pressure, and Heat-Sealing Duration - Christabel Jayastu Swadana Suhardi; Roma Juliana Arios; Annisa Raihanah Maimun; Mrr. Lukie Trianawati; Sistya Yurizka Zein; Shadylla Al-Mahra Granada; Resti Herwiyati; Muhammad Ihsan Sulaiman; Fauzan Hilmi; Annisa Triananda Dias Putri; Adit Napaulana; Wuliddah Tamsil Barokah (Batrisya Education, 2026)
The sealing process in candy packaging is crucial for maintaining product safety, quality, and stability. However, variations in temperature, pressure, and sealing time often cause inconsistencies in seal strength and defects when using conventional systems. This study applies the Mamdani fuzzy logic method to optimize temperature, pressure, and sealing duration for consistent seal quality. The input variables are Temperature, Pressure, and Duration, while the output variable, Seal_Conditions, includes “Less tight,” “Optimal,” and “Melt.” The fuzzy inference system consists of fuzzification, rule evaluation, and defuzzification using the centroid method. Nine fuzzy rules were developed to model the sealing behavior based on parameter interactions. The defuzzification result yielded a crisp value of 4.73, indicating a sufficiently tight seal without melting the packaging material. These findings demonstrate that the Mamdani fuzzy logic method effectively manages nonlinear variations in the sealing process, ensuring consistent product quality and minimizing defects and material waste. Therefore, fuzzy logic offers an adaptive and reliable control approach for optimizing the heat-sealing process in candy packaging.